Multitarget Drug Discovery for Alzheimer's Disease: Triazinones as BACE‐1 and GSK‐3β Inhibitors1. Issue 5 (11th December 2014) - Prati, Federica; De Simone, Angela; Bisignano, Paola; Armirotti, Andrea; Summa, Maria; Pizzirani, Daniela; Scarpelli, Rita; Perez, Daniel I.; Andrisano, Vincenza; Perez‐Castillo, Ana; Monti, Barbara; Massenzio, Francesca; et al.
Abstract Cumulative evidence strongly supports that the amyloid and tau hypotheses are not mutually exclusive, but concomitantly contribute to neurodegeneration in Alzheimer′s disease (AD). Thus, the development of multitarget drugs which are involved in both pathways might represent a promising therapeutic strategy. Accordingly, reported here in is the discovery of 6‐amino‐4‐phenyl‐3, 4‐dihydro‐1, 3, 5‐triazin‐2(1H)‐ones as the first class of molecules able to simultaneously modulate BACE‐1 and GSK‐3β. Notably, one triazinone showed well‐balanced in vitro potencies against the two enzymes (IC50 of (18.03±0.01) μM and (14.67±0.78) μM for BACE‐1 and GSK‐3β, respectively). In cell‐based assays, it displayed effective neuroprotective and neurogenic activities and no neurotoxicity. It also showed good brain permeability in a preliminary pharmacokinetic assessment in mice. Overall, triazinones might represent a promising starting point towards high quality lead compounds with an AD‐modifying potential.